The Role of SAARC in Economic Cooperation A Study of India–Pakistan Tensions that Hamper South Asian Regionalism - Habib Hanafi; M. Firli; M. Naufal Ghaniyyah Nail; Imanuddin Abdurrahman Jibril (Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pasundan, 2026)
The long-standing political tensions between India and Pakistan have been a major factor undermining the effectiveness of the South Asian Association for Regional Cooperation (SAARC) as a platform for economic integration in South Asia. Despite the region's enormous potential from its young population and vast domestic market to its opportunities for industrialization South Asian regionalism is operating far below its optimal capacity. This study analyzes how the India and Pakistan bilateral conflict hinders SAARC's function in promoting regional economic cooperation. Using the New Regionalism theoretical approach, this study shows that state dominance, the weak role of non-governmental actors, and the absence of conflict resolution mechanisms make SAARC vulnerable to stagnation whenever political tensions rise. The consensus mechanism that forms the institutional basis of SAARC also often becomes a structural obstacle because it allows India or Pakistan to veto the regional agenda. In addition, this study finds that small countries in South Asia are increasingly seeking integration alternatives outside SAARC due to the low predictability of regional cooperation. Various opportunities such as integration Energy, trade connectivity, and SME strengthening cannot be optimized due to rivalry between the two largest countries in the region. Thus, this study confirms that the functioning of SAARC is highly dependent on India-Pakistan political stability. Without improvement in relations between the two countries and institutional reform of SAARC, South Asian regionalism will remain stagnant compared to other regions such as ASEAN or the European Union. This study is expected to provide a deeper understanding of the structural challenges of SAARC while encouraging the formulation of regional strategies that are more adaptive, inclusive, and oriented towards collective economic cooperation.